Evaluating the Quality of Final Examination Question Paper in Engineering Education - Abirami, A. M.; Palaninatha Raja, M. (Journal of Engineering Education Transformations, 2020)
In recent years, there has been a downtrend in the pass percentage of UG Engineering Mathematics papers among students. Students find it difficult to score pass marks in the subject in the recent batches. Factors like lack of understanding in basic concepts, lack of quality of teaching, lack of quality in question papers, strict evaluation, and so on may be related to poor performance of students. Hence, it becomes necessary to examine the nature of final examination question papers, especially for the maths courses. It is essential to assess the type of questions asked in the examinations using the statistical techniques and measures. In this paper, the descriptive study has been made to evaluate the quality of question papers of Mathematics with the result data.